Objective Evaluation of the Treatment of Functional Disorders in Temporomandibular Joint by Means of Photo-registration - P. Tvrdý; J. Pazdera (Czech Dental Chamber, 2008)
In a group of 40 patients the authors demonstrated the method of objective examination of the function of temporomandibular joint. A simple measurement of the mouth by a ruler or a sliding ruler does not necessarily provide precise results and may not be identical when made by two individuals. The authors employed a method of recording the function of jaw joints by measuring the extent of abduction and lateral motion of mandible by means of photo-registration of the movements of lower jaw. The method was used for the evaluation of the results of mini-invasive therapy of dislocation of the joint disc.